1985
DOI: 10.2307/3576716
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic Transformation Is Enhanced by Multiple Low Doses of Fission-Spectrum Neutrons

Abstract: The neoplastic transformation of C3H mouse 10T1/2 cells was measured induced by fission-spectrum neutrons delivered at a high dose rate in five fractions over 4 days. The transformation frequency was significantly enhanced over that due to single equivalent total doses. These new data, in the low dose region, demonstrate an increased transformation frequency by fractionated versus single exposures of high-dose-rate fission-spectrum neutrons; an increase equal to that observed with low-dose-rate fission-spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…The observation of a reverse protraction factor for densely ionizing radiation is in line with a number of earlier experimental findings that suggest the possibility of enhanced effects of densely ionizing radiations in protracted or fractionated exposures (10)(11)(12)(13)(14). In human studies analogous relationships have been seen in uranium miners exposed to high levels of radon (75,17) and recently also in tin miners (18).…”
Section: Discussionsupporting
confidence: 76%
“…The observation of a reverse protraction factor for densely ionizing radiation is in line with a number of earlier experimental findings that suggest the possibility of enhanced effects of densely ionizing radiations in protracted or fractionated exposures (10)(11)(12)(13)(14). In human studies analogous relationships have been seen in uranium miners exposed to high levels of radon (75,17) and recently also in tin miners (18).…”
Section: Discussionsupporting
confidence: 76%
“…Hill et al (1985) found that five equal fractions of high-dose-rate fission-spectrum neutrons, delivered over a 4-day period, resulted in transformation frequencies of 10TI/2 cells consistent with the results with low dose-rates that had been reported earlier ; Jones et al . (1989) obtained similar results with Syrian hamster embryo cells ; and Redpath et al (1990 a, b) also observed enhanced transformation with a human-cell hybrid .…”
Section: Introductionsupporting
confidence: 90%
“…As was noted by Elkind and Hill (1986 a), a prediction of the Rossi/Kellerer model is that cells exposed to multiple dose fractions, at a high dose-rate, should achieve a transformation frequency significantly lower than what was observed by Hill et al (1985) . In addition, the Rossi/Kellerer model did not explain why the induction curves for low-dose-rate and multiple high-dose-rate exposures converged on the curve for single high-dose-rate exposures at high total doses (Hill et al .…”
Section: A Biophysical Modelmentioning
confidence: 81%
“…Both neutron and gamma irradiation are potential carcinogens, as demonstrated by the fact that both can transform cells in vitro (14)(15)(16) and induce tumors, including thymic lymphomas, in animals (17,18). One goal of this study was to determine whether the differences in qualities of these different forms of radiation might result in tumors with a different pattern of ras gene mutations.…”
Section: Comparison Between Different Forms Of Ionizing Radiation Intmentioning
confidence: 99%